Dekonstruksi Peran Seme dan Uke dalam Manga Shishi mo Kobamazu - Vanya Arisda Putri; Diana Puspitasari; Heri Widodo (Vocational College of Diponegoro University, 2022)
This research is descriptive qualitative research with the object of research manga entitled